2008
DOI: 10.3208/sandf.48.587
|View full text |Cite
|
Sign up to set email alerts
|

Shear Strength of a Soil Containing Vegetation Roots

Abstract: Vegetation can signiˆcantly contribute to stabilise sloping terrain by reinforcing the soil: this reinforcement depends on the morphological characteristics of the root systems and the tensile strength of single roots. This paper describes an investigation on the reinforcing eŠect of soil-root matrix in the laboratory using a modiˆed large shear box apparatus (300 mm×300 mm). Four diŠerent species of plant namely Vertiveria zizanoides, Leucaena leucocephala, Bixa orellana and Bauhinia purpurea were planted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 8 publications
2
32
0
1
Order By: Relevance
“…Whereas Delft3D can adjust the flow roughness depending on vegetation characteristics, it does not directly increase the critical shear stress for erosion (Deltares, 2014). However, studies have shown that there is a strong effect of plant roots on the critical shear stress for erosion through enhanced shear strength of the substrate (Ali & Osman, 2008;Tengbeh, 1989;Watts et al, 2003). We include vegetation with a simple routine that adjusts the critical shear stress for erosion and the flow roughness depending on the local water depth, an important factor in plant survival.…”
Section: Matlab Vegetation and Soil Consolidationmentioning
confidence: 99%
“…Whereas Delft3D can adjust the flow roughness depending on vegetation characteristics, it does not directly increase the critical shear stress for erosion (Deltares, 2014). However, studies have shown that there is a strong effect of plant roots on the critical shear stress for erosion through enhanced shear strength of the substrate (Ali & Osman, 2008;Tengbeh, 1989;Watts et al, 2003). We include vegetation with a simple routine that adjusts the critical shear stress for erosion and the flow roughness depending on the local water depth, an important factor in plant survival.…”
Section: Matlab Vegetation and Soil Consolidationmentioning
confidence: 99%
“…Ali et al [11] studied the shear strength of soil containing vegetable roots and noticed that after 6 months, under soil suction-free condition, the root of Leucaena leucocephala could increase the cohesion of soil by 116 (0.1 m), 225.0 (0.3 m) and 413.4% (0.5 m), which increases the shear strength of the soil to improve the stability of the bank. In addition, the Vetiver grass root system has high tensile and shear strength, and this unique property would increase the soil shear strength.…”
Section: Slope Stability Effectmentioning
confidence: 99%
“…Previous studies have proved that Vetiver grass (Vetiveria zizanioides) has a high ability to increase the stability of the soil slope. Ali et al [11] showed that Vetiver grass, due to its unique root characteristics, could increase the shear strength of the soil and improve the stability of the bank slope. Many existing ecological engineering works have proved the feasibility, ecological restoration, and bank slope stable effectiveness of the ecological revetment and Vetiver grass.…”
Section: Introductionmentioning
confidence: 99%
“…Nwoke et al (2016a) reported that maximum uprooting force has a linear relationship with stem basal diameter. Several studies have demonstrated that uprooting resistance significantly influence the soil reinforcement capability of plants (Normaniza et al, 2008;Ali and Osman, 2008;Ali, 2010;Osman et al, 2011;Saifuddin et al, 2015). Our data showed that the maximum uprooting resistance of sea hibiscus plants is significantly higher than Australian pine plants, suggesting a superior root anchorage capability by sea hibiscus plants.…”
Section: Root Anchorage Capabilitymentioning
confidence: 99%